Conceptual Metaphors on Thai Websites Used by Thai Speakers: A Cognitive Linguistic Study of Conceptual Metaphors and Mapping Processes in the Internet System - Khotchaphet, Suwatchai (Ratchaphruek Journal, 2025)
This research aims to investigate the types of conceptual metaphors found on Thai websites used by Thai speakers and to analyse the mapping processes of these metaphors within the framework of Cognitive Linguistics. Data were collected from 180 websites and categorised into 18 content types. The findings reveal that conceptual metaphors used by Thai speakers can be classified into eight categories: (1) human metaphors, (2) action metaphors, (3) object metaphors, (4) war metaphors, (5) print media metaphors, (6) body-part metaphors, (7) construction metaphors, and (8) nature metaphors. Furthermore, the study indicates that the mapping processes of these eight metaphor types follow a consistent pattern, monolinear mapping, also referred to as ontological correspondences. This process involves projecting conceptual relationships concerning the state or condition of entities within the cognitive framework of language users, thereby transferring meaning from a source domain to a target domain. The study underscores how conceptual metaphorization is shaped by human experience and socio-cognitive structures, offering insights into the interplay between language, thought, and cultural context.